2006
DOI: 10.1158/1078-0432.ccr-06-0231
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Apoptosis in Rectal Cancer Patients of the Dutch Total Mesorectal Excision Trial: Radiotherapy Is Redundant in Intrinsically High-Apoptotic Tumors

Abstract: Purpose: The combination of radiotherapy and good quality surgery reduces local recurrence rate for rectal cancer patients. This study assesses the prognostic value of both intrinsic and radiotherapy-induced apoptosis and evaluates the relevance of radiotherapy for outcome of rectal cancer patients. Experimental Design: Tumor samples (1,198) were available from the Dutch Total Mesorectal Excision trial, in which rectal cancer patients were treated with standardized surgery and randomized for preoperative shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 26 publications
(28 reference statements)
1
43
2
Order By: Relevance
“…As the benefit of radiation therapy is, at least in part, mediated by the induction of tumor cell apoptosis and other forms of cell death (20,31,32), it is not surprising that the majority of these markers involve proapoptotic or antiapoptotic proteins. A recent study evaluated the predictive value of tumor cell apoptosis as quantified by immunohistochemical staining of paraffin-embedded tumor tissue arrays with the M30 antibody in rectal cancer specimens from the Dutch TME trial (19). In this study, the number of M30-positive cells showed to be a significant predictor of local recurrence but with at much lower levels of statistical significance than we found measuring caspase-3 activity.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…As the benefit of radiation therapy is, at least in part, mediated by the induction of tumor cell apoptosis and other forms of cell death (20,31,32), it is not surprising that the majority of these markers involve proapoptotic or antiapoptotic proteins. A recent study evaluated the predictive value of tumor cell apoptosis as quantified by immunohistochemical staining of paraffin-embedded tumor tissue arrays with the M30 antibody in rectal cancer specimens from the Dutch TME trial (19). In this study, the number of M30-positive cells showed to be a significant predictor of local recurrence but with at much lower levels of statistical significance than we found measuring caspase-3 activity.…”
Section: Discussionmentioning
confidence: 48%
“…Caspase-3 activity in the current study was evaluated in nonirradiated tumors, as several studies have convincingly showed that radiation therapy -induced apoptosis is not of prognostic value (17,19). Evaluation of enzymatic caspase-3 activity as an indicator of apoptotic cell death seemed in this study an accurate variable for prediction of local recurrences.…”
Section: Discussionmentioning
confidence: 80%
“…Tissue microarrays from formalinfixed, paraffin-embedded tumors included in the Dutch TME trial were constructed with a custom-built precision tissue arrayer (Beecher Instruments) using a 2-mm-diameter punch as described previously (20).…”
Section: Methodsmentioning
confidence: 99%
“…Tumor staging was determined with the tumor-node-metastasis (TNM) classification (15). Paraffin-embedded tumors (1,047) were available in tissue microarray format, as previously described (16). Patients who were ineligible (n = 25) or TNM stage 0 (n = 6) were excluded from the analyses, leaving 1,016 patients for evaluation of the prognostic value of HLA-DR expression.…”
Section: Methodsmentioning
confidence: 99%